Trend of utilization of safe motherhood services in rural Nepal - Dangal, Binod; Uprety, Arun; Khati, Karuna; Thapa, Roshan Kumar; Shrestha, Ramesh; Lamichhane, Reena; Khadka, Himshail; Kalaunee, SP; Khadka, Shyam (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: The government of Nepal has implemented Safe Motherhood programs throughout the country to decrease the perinatal morbidity and mortality. Safe motherhood service includes normal vaginal delivery, Caesarian Section (CS) and perinatal management. CS rates are a major public concern. Currently 18.6% of all births occur by CS, ranging from 6 to 27.2% in different parts of the world. Method: Retrospectively collected data from Electronic Health Record (EHR) of Bahmini deliveries from May 1,2016 to October 31,2020 were used. Demographic profiles like age, geographical location. Similarly, gestational age, caste, gravida, parity, various indications of CS, maternal, fetal, and neonatal outcomes were also recorded. Result: A total of 4168 deliveries were conducted over four and half years with 3694 (88.6%) vaginal deliveries and 474 (11.4%) CS. There was constant maintenance of CS rate from 5-15% over four and half years, 11% in 2016 to 12% in 2019. Fetal distress was the commonest indication of overall CS followed by non-progress of labor. The women from Bhimeshwor municipality of Dolakha district, were 156 (32.9%). The most CS was done in the age group of 20-24 years, which was 192 (40.5%). Neonatal Death was 3/1000 births. Conclusion: Different from the other evidences, we found that our CS rate was within the limit of WHO’s recommendation for lower resource setting. Following strict guidelines and with dedicated care, it’s possible to maintain recommended CS rate with less neonatal and maternal morbidities even in lower resource setting where there are no NICU, ICU facilities and Electronic Fetal Monitoring (EFM).